Pengembangan Media Belajar Handout Flipbook untuk Meningkatkan Hasil Belajar Estimasi Biaya Konstruksi - Mirotus Sakdiah; Diana Manzil; Lutfia Santika Dewi; Rubbayyi Shaffiyyah; Nila Rahmawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Effective teaching of Construction Cost Estimation in vocational secondary education, aimed at producing competent estimators, is still hampered by a gap between ideal teaching practices and reality. In this study, this gap was addressed through the development of teaching materials to enhance student learning outcomes. The study utilised the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop the ‘Handout Flipbook’ learning resource. The objective of this study was to produce an effective learning resource by analysing its suitability through the completion of a validation sheet, a student response questionnaire, and an analysis of learning outcomes between the control and experimental classes. The feasibility analysis of the media, assessed using a likert scale, indicated that the media is highly suitable. The analysis of student responses revealed 97% positive responses, which fall into the ‘highly effective’ category. Analysis of learning outcomes using the N-Gain test showed a percentage of 75. 21 in the experimental class, indicating that the use of media in the experimental class was quite effective, with an average increase in learning outcomes of  45.83, whilst the use of conventional media in the control class was classified as ineffective, with a percentage value of 38.86 and an increase of 21.45; the Mann-Whitney test showed a significant difference between the control and experimental classes, with an Asymp. Sig. (2-tailed) <0.05, with superior average learning outcomes in the experimental class. This triangulation of analyses indicates that the Flipbook Handout medium is effective in improving students’ learning outcomes.